Down syndrome with congenital hydrocephalus: case report Síndrome de Down associada a hidrocefalia congênita: relato de caso - Cassiano Mateus Forcelini; Adroaldo Baseggio Mallmann; Paulo Sérgio Crusius; Cláudio Albano Seibert; Marcelo Ughini Crusius; Denise Isabel Zandoná; Charles Carazzo; Cassiano Ughini Crusius; Eduardo Goellner; Jean Ragnini; Luciano Bambini Manzato; Gustavo Winkelmann; et al. (Arquivos de Neuro-Psiquiatria)
Down syndrome is the most frequent genetic cause of mental retardation. Although usually presenting dysmorphic features and organ malformations, it is rarely associated with congenital hydrocephalus. The case of male neonate whose hydrocephalus was detected since the pregnancy and was discovered to have the syndrome at birth is reported. Chromosomal analysis confirmed the genetic disorder, and hydrocephalus was treated with ventriculoperitoneal shunt because of abnormal increase of head circumference. The patient has been accompanied and his development is considered normal when compared to the expected for those affected by the syndrome. A síndrome de Down é a causa genética mais freqüente de retardo mental. Embora comumente apresentando dismorfias e malformações de órgãos, raramente está associada à hidrocefalia congênita. O caso de um recém-nascido masculino cuja hidrocefalia foi detectada desde a gravidez e que se descobriu ser portadora da síndrome ao nascimento é relatado. O cariótipo confirmou a anormalidade genética, e a hidrocefalia foi tratada com derivação ventriculoperitoneal devido ao aumento anormal do perímetro cefálico. O paciente está sendo acompanhado e seu desenvolvimento é considerado normal quando comparado ao esperado para os portadores da síndrome.